GntP Is the Escherichia coli Fructuronic Acid Transporter and Belongs to the UxuR Regulon - Bates Utz, Cristina (American Society for Microbiology, 2004)
Escherichia coli has four gluconate transporters, GntP, GntU, GntT, and IdnT, which are members of the major facilitator superfamily. The physiological function of GntP was previously unknown and is the subject of this study. GntP is not induced by gluconate, and despite being located adjacent to genes involved in glucuronate catabolism, gntP does not encode a glucuronate transporter. Here we identify gntP as the gene which encodes the fructuronate transporter. We show that gntP is induced by fructuronate and is a new member of the UxuR regulon: gntP is derepressed in an uxuR strain, UxuR binds in vitro specifically to an operator site that overlaps the gntP promoter, and UxuR binding is eliminated by fructuronate. Transcription of gntP requires activation by cyclic AMP (cAMP)-cAMP receptor protein. A gntP mutant cannot grow on fructuronate but grows normally on glucuronate and gluconate. Thus, the UxuR regulon is a module of sugar acid catabolism whose physiological role is for growth on fructuronate. Glucuronate, because it proceeds through a fructuronate intermediate, must induce the UxuR regulon and must also induce the ExuR regulon, which encodes the glucuronate transporter, ExuT, and the first step in its catabolism, UxaC. Thus, hexuronate catabolism in E. coli requires both the ExuR and UxuR regulons, while fructuronate catabolism requires only the UxuR regulon.